2008
DOI: 10.1063/1.2912461
|View full text |Cite
|
Sign up to set email alerts
|

Selective formation of turbulent structures in magnetized cylindrical plasmas

Abstract: The mechanism of nonlinear structural formation has been studied with a three-field reduced fluid model, which is extended to describe the resistive drift wave turbulence in magnetized cylindrical plasmas. In this model, ion-neutral collisions strongly stabilize the resistive drift wave, and the formed structure depends on the collision frequency. If the collision frequency is small, modulational coupling of unstable modes generates a zonal flow. On the other hand, if the collision frequency is large, a stream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
81
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 24 publications
3
81
0
Order By: Relevance
“…The ionneutral collision frequency in has the stabilization effect of the resistive drift wave and is also related to zonal flow damping, which gives a selection rule of turbulent structure formation such as zonal flows and streamers. 3 Simulations are carried out with a time independent particle source, whose profile is given as…”
Section: B Simulation Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The ionneutral collision frequency in has the stabilization effect of the resistive drift wave and is also related to zonal flow damping, which gives a selection rule of turbulent structure formation such as zonal flows and streamers. 3 Simulations are carried out with a time independent particle source, whose profile is given as…”
Section: B Simulation Parametersmentioning
confidence: 99%
“…1,2 There exist zonal flows and streamers, which suppress and enhance the transport, respectively, in meso-scale structures, and their selection rule has been investigated. 1, 3 Large scale vortex has been found to be also driven by turbulence. [4][5][6][7] Other nonlinear coherent structures formed by the drift waves, such as drift solitons, have been studied.…”
mentioning
confidence: 99%
“…In the Large Mirror Device Upgrade (LMD-U), the fluctuation spectra change depending on the neutral pressure because of drift wave damping through collisions with neutral particles [9][10][11]. In this paper, we report differences in the radial profiles of the density fluctuation PDF in two different turbulent states.…”
Section: Introductionmentioning
confidence: 96%
“…The streamer structure was initially predicted by an analytical study that exhibited importance of the nonlinear coupling between drift waves and a nonlinearly excited global mode the so-called mediator [11]. Dedicated studies for analyzing the nonlinear coupling in density fluctuations demonstrated the reliability of the predicted model [6][7][8]12]. Moreover, a selection rule between the streamers and the zonal flows was proposed in numerical simulation study, showing the importance of the ionneutral collisional damping of drift waves [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a set of experiments using linear devices such as the Large Mirror Device (LMD), the Large Mirror Device-Upgrade (LMD- The streamer is characterized by a structure radially stretched and azimuthally localized, as reported in Refs. [6][7][8]. The existence of the streamers in magnetically confined plasmas is foreseen to reduce the plasma performance, since the streamers act as a radially elongated large convective cell.…”
Section: Introductionmentioning
confidence: 99%